Understanding School Refusal : a Handbook for Professionals in Education, Health and Social Care. - Thambirajah, M. S. (Jessica Kingsley Publishers, 2007)
School absenteeism is a huge problem in education and this book focuses in particular on children who experience 'school phobia' or 'school refusal' as opposed to those who choose to truant. School refusal is a crippling condition in which children experience extreme anxiety or panic attacks when faced with everyday school life and this handbook aims to explore and raise awareness of the problem of school refusal in children and young people, and provide plans and strategies for education, health and social care professionals for identifying and addressing this problem. Combining educational a.